Implementation of Enforcement of Regional Regulations (PERDA) in the Implementation of Public Peace and Order and Community Protection in Sinjai Regency - Baharuddin Baharuddin; Alifa Nailatul Izzah; Makmur Makmur (PINISI Discretion Review, 2022)
Local regulation concerning the Implementation of Public Peace and Order and Community Protection aims to realize the order of life in society, nation and state which ensures that every person or entity can carry out their rights and obligations in a harmonious and balanced manner. The location of the research was carried out at the Civil Service Police Unit and the Sinjai Regency Fire Department. This study aims to determine the implementation of local regulation enforcement (PERDA) in the implementation of public peace and order and community protection in Sinjai Regency. The approach used in this research is qualitative. Data collection techniques used are observation, interviews, and documentation. The data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that the implementation of Regional Regulation Enforcement (PERDA) in the administration of peace and public order as well as the protection of the community in Sinjai Regency with a focus on communication research, bureaucratic structure, resources, and disposition goes well and effectively.